Evaluasi Kualitas Nutrien Dedak Padi di Provinsi Jawa Barat Berdasarkan Perbedaan Musim terhadap Standar Nasional Indonesia: The Nutrient Quality Evaluation of Rice Bran in West Java Province Based on Seasonal Differences Against Indonesian National Standards - Wibowo, I B; Permana, Idat Galih; Nahrowi (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
This research aimed to analyze differences in the nutrient quality of rice bran during the rainy and dry seasons at all user levels in West Java Province for the 2016-2020 period compared to SNI 3178 in 2013. This research used secondary data from 306 samples from two laboratories, Feed Quality and Certification (BPMSP) Bekasi and Feed/Feed Ingredient Quality and Safety Testing Center (BPMKP/BP) Cikole Lembang, West Java. this study, used frequency distribution to provide a simple description of data collection, in contrast, rice bran users used percentages of test data suitable for rice bran according to SNI 3178 of 2013. The results showed that the conformity of rice bran nutrients to SNI in the dry season was better compared to the rainy season. The best percentage of SNI conformity at the rice bran user level was large users, suppliers, small users, and other users respectively. Key words: quality of rice bran, rice bran, SNI rice bran